The effect of morphology and cobalt concentration on the sensing properties of zinc oxide sputtered films - Calderon, Yormary Nathaly Colmenares (2018)
The use of semiconductor materials applied in gas sensing devices is currently one of the most researched topics in air quality control and environmental protection. The research is focused on the production of new sensing materials with improved detection limits, selectivity, working temperatures and response times of the known semiconductor materials. Although theoretical models show the great importance of morphology on gas detection, a direct relation between structure size/morphology and the gas sensing properties has not been experimentally established. In this work, Radio Frequency-sputtering method is used to deposit and produce zinc oxide thin films from ceramic and metallic targets, in which the latter are submitted to thermal oxidation to obtaining ZnO porous films. The samples are deposited on platinum interdigitated electrodes and the electrical behavior is analyzed when exposed to ozone. The effects of feature size and film porosity are studied regarding the enhancement of sensor performance. The results show sensors with small features and low porosity present low ozone sensitivity and fast response; while greater features in highly porous films exhibit low sensitivity and slower responses. The optimum sensing performance is found to be somewhere between when the apparent surface area available for adsorption is maximized and the best ozone response is registered. On the other hand, the electrical behavior of doped films when exposed to ozone demonstrates cobalt presence plays a fundamental role. By inserting cobalt, we could improve the sensor response by 62% under the same conditions. However, the increase of doping concentration modify the zinc oxide conductivity to p-type and drastically decrease the sensor response due to the possible formation of cobalt oxide segregates. Our results propose RF sputtering deposition as a versatile technique in the production of semiconductor gas sensors, once high porosity and, therefore, sensitivity can be controlled through the deposition of metals, and dopants, followed by thermal oxidation.